The Effect of Everyday Moral Sensitivity on Bullying Bystander Behavior: Parallel Mediating Roles of Empathy and Moral Disengagement - Xie, Zhongju (Journal of interpersonal violence, 2023)
The higher moral sensitivity to bullying a student has, the more likely they are to help the victim or inhibit bullying rather than ignore it. Research has mainly focused on particular sensitivity to bullying, and it remains unknown whether sensitivity to everyday moral issues functions similarly. The present study aimed to examine the effect of everyday moral sensitivity (EMS) on bullying bystander behaviors. We included a range of school children (n = 1,655, Grades 3–12, 27.6% girls) in Southwest China. The results show 6.10% have been a victim-only, 0.48% have been a bully-only, 0.85% have been the bullying victim, 92.57% have been neither a bully nor a bullying victim, and 45.86% have observed bullying. Students in lower grades are more likely to be bullied. After controlling for covariates (i.e., gender, grade, and social desirability), EMS is positively associated with positive bystander behaviors. Moreover, empathy and moral disengagement (MD) play a mediating role in the relationship between EMS and positive bystander behaviors. The results reveal two parallel processes of EMS influenced bystander behaviors (i.e., empathy and MD). The findings indicate the possibility of cultivating EMS and highlight the role of morality development in preventing school bullying.